Perbaikan User Interface Menggunakan Usability Testing dan Pendekatan Human-Centered Design - Tasya Mina Alifia; Nugroho Purnomo Aji; Ahmad Arfan Arsyad; Lutfi Rahmatuti Maghfiroh (Politeknik Statistika STIS, 2021)
In the middle of the rapid advancement of technology and use of internet, Badan Narkotika Nasional (BNN) as a government agency built a website for the benefit of information dissemination and communication acceleration for public. This research focused on evaluation and improvement of the BNN official website’s user interface using Usability Testing and Human-Centered Design (HCD) Approach. The research is started with user’s identification, user’s requirement analysis, original design usability testing evaluation, solution design production, and solution design usability testing evalution. The result of this research showed the use of HCD approch improved usability in efectivity and eficiency aspects with 96% each on original design increased to 100% on solution design. Furthermore, the average length of time for usability testing tasks is faster from 45,28 seconds ond original design to 9,36 seconds on solution design.